Peran Inspektorat Daerah Dalam Pembinaan dan Pengawasan Pengelolaan Dana Desa di Kabupaten Soppeng - Ahmad Fajri (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2024)
More optimal guidance and supervision in the management of village funds is an important agenda to carry out so that deviations and misuse can be avoided. The role of the Regional Inspectorate in supervising and guiding the management of Village Funds in Soppeng Regency is very important to ensure that the use of Village Funds is on target and can be accounted for. This research uses a qualitative descriptive research method. The data collection techniques used were observation, interviews and documentation. The research location was at the Inspectorate office in Soppeng district and samples were taken in three villages, namely Belo village, Mattabulu village and Rompegading village, Soppeng district. The research results show that the Regional Inspectorate has an important role in the development and supervision of village funds in Soppeng Regency. In coaching, the inspectorate functions as a facilitator who provides training and counseling, technical assistance, and follow-up on inspection results to village officials. Apart from that, the role of the Soppeng Regency Regional Inspectorate in carrying out supervision is through auditing and examining village financial reports as well as monitoring and evaluating the implementation of programs and activities funded by village funds. However, limited human resources and lack of APIP capacity are obstacles in providing optimal and comprehensive guidance and supervision of the management of the Soppeng Regency Village Fund. Apart from that, cooperation with related parties such as the Financial and Development Audit Agency (BPKP) and the Community and Village Empowerment Service (DPMD) needs to be increased to strengthen supervision and guidance so that village fund management can be transparent and accountable.